Perkembangan dan Implementasi Psikologi Pendidikan dalam Proses Pendidikan dan Pembelajaran - Sari, Filma Alia; S, Neviyarni; Afdal; Rizka, Mifta (CV Global Research Publication, 2025)
This review study is motivated by the rapid development of educational psychology theories and practices that have significantly influenced contemporary learning processes. The purpose of this research is to examine how psychological theories are implemented in current educational and instructional practices, with a specific focus on teacher interventions, feedback, technology use, student and educator well-being, and contextual factors affecting effectiveness. The research employs a Systematic Literature Review (SLR) of scholarly publications from 2010 to 2025. The review findings indicate that although theoretical advancements in educational psychology have been substantial, their implementation in practice is often constrained by limited teacher training, inadequate resources, and insufficient institutional support. Furthermore, there remains a research gap concerning long-term evaluation and the impact of educational psychology beyond traditional school settings, such as in extended education programs. The study concludes that to enhance the impact of educational psychology, implementation approaches must prioritize fidelity, contextual adaptation, and sustained professional support.